Faktor Determinan Kepatuhan Konsumsi Tablet Tambah Darah pada Siswi SMP Berdasarkan Teori Perilaku Terencana - Dewi Sri Sumardilah; Kadek Dwi Ratna Kemala; Gading Quinta Wangi (Nutrition Department, Poltekkes Kemenkes Tanjung Karang, 2025)
Iron deficiency anemia remains a major nutritional problem among adolescent girls, caused by low dietary iron intake and monthly menstrual blood loss. To prevent anemia, the Indonesian government has implemented a weekly iron supplementation program (Tablet Tambah Darah, TTD) for school-aged girls since 2014. However, adherence to TTD remains low, limiting program effectiveness. Adherence is influenced by students’ attitudes, support from parents or teachers, and perceived behavioral control. This study aimed to examine the relationship between attitudes, subjective norms, and perceived behavioral control with TTD adherence among adolescent girls. A cross-sectional study was conducted at SMP Kartika II-2 Bandar Lampung, including the total population of seventh- and eighth-grade female students (n = 73). The dependent variable was TTD adherence, measured using the Morisky Medication Adherence Scale-8 (MMAS-8), while independent variables included attitude, subjective norms, and perceived behavioral control. Data were analyzed using the chi-square test. Results showed that 65.8% of students were non-adherent to TTD. Significant associations were found between attitude (p = 0.044; OR = 1.8), subjective norms (p = 0.010; OR = 2.3), and perceived behavioral control (p = 0.000; OR = 3.6) with adherence. It is recommended that schools, through teachers and school health staff, implement a structured weekly TTD schedule and enhance supervision to improve adherence among students